The Biodiversity of Edible Flowers: Discovering New Tastes and New Health Benefits - Benvenuti, Stefano; Mazzoncini, Marco (Frontiers in Plant Science, 2021)
Floriculture and horticulture have always been two parallel and very distinct agronomic realities. Floriculture is concerned with meeting the ornamental needs of our urban ecosystems, while horticulture is based on meeting food requirements. These two activities have now converged towards a food chain where flowers are conceived of as a sort of "new vegetable" and one of the most promising novelties to satisfy the growing need for food innovation both in terms of an organoleptic and nutraceutical profile. This novelty has rapidly evolved, especially following the growing scientific evidence of the human health benefits of flowers used as food. The typically high pigment concentration of the corollas (especially flavonoids and carotenoids), which have evolved to chromatically attract pollinators, indicates a marked nutraceutical activity especially in terms of antioxidant power. The use of flowers as food is not however, a new discovery, but a rediscovery of ancient ethnobotanical traditions. In fact, the Greeks and Romans used flowers both to give a surprising ornamental impact to various dishes (for example, rose petals in ancient Rome) and to enhance the organoleptic synergy between the taste of traditional foods (vegetables, meat, fish, etc.) and that of flower aromas. However, the gastronomic use of flowers has been limited to and dependent on the relatively narrow, seasonal timeframe in which these flowers proliferate almost exclusively in natural ecosystems. The use of mallow (Malva sylvestris), borage (Borago officinalis) and acacia (Robinia pseudoacacia) flowers are the best known examples of an appreciated but "season-dependent" food potential of flowers. Today this problem of seasonality has been gradually attenuated by an "agronomic conversion" of flower species that were traditionally cropped exclusively as ornamentals towards their cultivation for food purposes. Since this innovative agronomic chain intended for human consumption is recent, it is often not clear which species are actually edible and which are potentially toxic or even poisonous. The benefits, contraindications and potential toxicity of the biodiversity of wild flowers need to be clarified and so that there can be a focus on those suitable for food.